2012
DOI: 10.1186/2008-2231-20-9
|View full text |Cite
|
Sign up to set email alerts
|

Levels of organophosphorus pesticides in medicinal plants commonly consumed in Iran

Abstract: The frequent occurrence of pesticide residues in herbal materials was indicated by previous studies. In this study, the concentration of some of the organophosphorus pesticides including parathion, malathion, diazinon and pirimiphos methyl in different kinds of medicinal plants were determined. The samples were collected randomly from ten local markets of different areas of Iran. At the detection limit of 0.5 ng g-1, parathion and pirimiphos methyl were not detected in any of the samples. Some amounts of malat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Consistently with our results, the major essential oil components of P. olivieri collected in northern part of Iran (Mazandaran and Guilan provinces) were germacrene D, b-caryophyllene, and a-pinene, [14] while Ghassemi et al [15] found hexahydrofarnesyl acetone, spathulenol, germacrene D, b-caryophyllene, and caryophyllene oxide as main constituents in the essential oil of P. olivieri collected from central Iran (Isfahan province). In another report [16] on populations from Damav (Tehran province), the main compounds were germacrene D, b-caryophyllene, a-pinene, and b-selinene.…”
Section: Composition Of the Essential Oilssupporting
confidence: 91%
“…Consistently with our results, the major essential oil components of P. olivieri collected in northern part of Iran (Mazandaran and Guilan provinces) were germacrene D, b-caryophyllene, and a-pinene, [14] while Ghassemi et al [15] found hexahydrofarnesyl acetone, spathulenol, germacrene D, b-caryophyllene, and caryophyllene oxide as main constituents in the essential oil of P. olivieri collected from central Iran (Isfahan province). In another report [16] on populations from Damav (Tehran province), the main compounds were germacrene D, b-caryophyllene, a-pinene, and b-selinene.…”
Section: Composition Of the Essential Oilssupporting
confidence: 91%
“…The literature describes many analytical methods available for the determination of pesticide residues in plant material and soil samples. To a large extent, these methods are based on traditional approaches: soxhlet extraction [14][15][16] , solid phase extraction 17,18 , pressurised liquid extraction 19,20 , matrix solid-phase dispersion 21,22 , solid-phase microextraction 23,24 , or dispersive liquid-liquid microextraction 25 . Currently, the QuEChERS procedure 26 is one of the most commonly used analytical methods for the determination of pesticides residues, and frequently this procedure is modified in terms of amounts and types of reagents, as well as available equipment [27][28][29][30] .…”
mentioning
confidence: 99%
“…Similarly, microbial contaminations and insect infestations also induce marked variation in the chemical profile of herbs and herbal products (Kneifel et al , 2002, Romagnoli et al , 2007, Tassaneeyakul et al , 2004. In addition, uncontrolled use of pesticides and systemic accumulation of toxic pollutants in cultivated medicinal plants inevitably impose critical risks to assuring the quality of herbal products (Cheng et al , 2013, Dogheim et al , 2004, Kosalec et al , 2009, Sarkhail et al , 2012, Zuin and Vilegas, 2000. Systemic and deliberate adulteration with foreign plant material and mixing of old or otherwise exhausted plant material along with the use of other foreign material further intensify the risks of blending unrelated and, in many cases, seriously hazardous chemical entities in herbal products (Foster, 2011).…”
Section: Phytochemical Variation Is a Common Phenomenon In Medicinal mentioning
confidence: 97%